2013
DOI: 10.5455/pmb.1-1333353810
|View full text |Cite
|
Sign up to set email alerts
|

What do Male Students at the College of Medicine of the University of Malawi Say About Semen Donation?

Abstract: Aim This study was aimed at assessing knowledge and attitude to semen donation among male students at the College of Medicine. Methods A semi-structured questionnaire survey of students doing Pre-Medical Sciences, MBBS, Pharmacy, Physiotherapy, and Medical Laboratory Science degrees at the College of Medicine. There were 180 respondents who took part in this study. Their ages ranged from 15 to 43 years with a mean of 21.21 years. Results A total of 130 (72.2%) of the respondents were aware of the practice of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the systematic overview by Van den Broeck [2], only one study focused exclusively on non-donors and two studies included both nondonors and actual or potential donors. After a thorough search, some additional studies on attitudes of non-donors were found: Lampiao, 2013 [3] in Malawi, Hedrih and Hedrih, 2012 [4] in Serbia and Onah et al, 2008 [5] in Nigeria. These studies came from countries in which few studies are performed about assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…In the systematic overview by Van den Broeck [2], only one study focused exclusively on non-donors and two studies included both nondonors and actual or potential donors. After a thorough search, some additional studies on attitudes of non-donors were found: Lampiao, 2013 [3] in Malawi, Hedrih and Hedrih, 2012 [4] in Serbia and Onah et al, 2008 [5] in Nigeria. These studies came from countries in which few studies are performed about assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…More than 3/4 of the couples have a long-lasting infertility. We have noticed a very long medical cursus, as in all the studies conducted in developing countries [6] [7] (Table 4).…”
Section: Epidemiologymentioning
confidence: 86%
“…Oocyte donation can be a good treatment option incancer treatment, premature ovarian failure, peri-and postmenopausal women, carriers of severe X-linked diseases, inefficient oocytes and/or unqualified embryo and failures in previous interventions and/or more than one failures. However, lack of awareness and misconceptions about sperm donation have negative effects 5 . In addition, due to cultural beliefs and norms considering sperms as keys for transmission of ancestry and kinship, sperm donation is not considered as sexually and morally acceptable 6 .However, in Kuwait, a Muslim country, it is legal to freeze sperms.…”
Section: Introductionmentioning
confidence: 99%